Observational study on weberian ethics in the film Sophie’s Choice - Matos, Fátima Regina Ney (2018)
When ethical dilemmas of responsibility and conviction seem to involve any human fabric of the real world, Sophie’s Choice (1982) is guided by an ethic of responsibility of one end would justify the means and she did not have the option to dodge out. Through an observational study of qualitative approach we aim to situate the dilemma suffered by the protagonist of the film within ethical parameters defined by Max Weber when he explains the ethics of responsibility and the conviction ethic. The contributions of this study go beyond the fictional and cinematic limits of Sophie’s Choice to a time depicting ethical dilemmas that may be suffered by people in the real world and (unwanted) choices reflecting further consequences beyond the end of justifications and axiological assumptions. Thus many other hodiernal historical contexts are diverse, that even in different political, cultural, economic and social conditions, people find themselves forced to make choices that are not intended. This widens the scope of the film and brings the contemporary debate that remains current.